Socialization of Legal Protection and the Impacts of Sexual Abuse on Women in Neglasari Village, Katibung Subdistrict, South Lampung Regency - Anggelika, Alissa Zahara; Alyana, Putri; Kania, Alkatya; Apriyanti, Deviola; Irawan, Fauza Subhan; Rifa’i, Miftakhhul; Hutasoit, Niko Greinaldi (Research and Social Study Institute, 2025)
Sexual abuse is one of the most common forms of violence experienced by women in Indonesia. The socialization in this community services activity aims to provide knowledge and understanding for women and adolescents in Neglasari Village, Katibung Subdistrict, South Lampung Regency about legal protection and the potential impacts of sexual abuse on women. The socialization activity took place at Sumbangsih Education Foundation Junior High School in Neglasari Village, Katibung Subdistrict, South Lampung Regency by involving 80 participants. The findings reveal that participants’ knowledge and understanding about legal protection and the impacts of sexual abuse on women increased after attending the material presentation and participating in the discussion. Initially, the knowledge of these junior high school students in Neglasari Village regarding sexual abuse on women was still low, indicated by their level of understanding ranging from 20 to 33% for all questions given. However, their level of understanding increased to 65 to 80% after the socialization, indicating that their knowledge and understanding about legal protection and the impacts of sexual abuse on women increased after attending the material presentation and participating in the discussion.